The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.4178/epih.e2021070
|View full text |Cite
|
Sign up to set email alerts
|

Dengue and COVID-19 infections in the ASEAN region: a concurrent outbreak of viral diseases

Abstract: The countries of the Association of Southeast Asian Nations (ASEAN) have been dealing with dengue outbreaks for decades, being one of the regions with high dengue infection cases globally. These outbreaks are happening on top of the COVID-19 pandemic that is causing havoc among these ten countries. Both infectious diseases have caused a tremendous burden for the countries in the region-from infection control to the economic impact. This increasing number of cases happened with the contribution of the disruptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…According to the Indian database, approximately 7.03% of the total population has been fully vaccinated against COVID-19 with the first and second dose in late July 2021 [91,92]. In other ASEAN countries, Cambodia and Malaysia have the secondhighest rate of inoculation at 47%, followed by 11% and 7% in the Philippines and Vietnam of vaccination rates, respectively of the entire population [34,93]. Due to the shortage of vaccination, the under-health care system and other influencing factors such as misdiagnosis, false-positive results hinder the control of dengue and COVID-19 [94].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Indian database, approximately 7.03% of the total population has been fully vaccinated against COVID-19 with the first and second dose in late July 2021 [91,92]. In other ASEAN countries, Cambodia and Malaysia have the secondhighest rate of inoculation at 47%, followed by 11% and 7% in the Philippines and Vietnam of vaccination rates, respectively of the entire population [34,93]. Due to the shortage of vaccination, the under-health care system and other influencing factors such as misdiagnosis, false-positive results hinder the control of dengue and COVID-19 [94].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have shown the relationship between the impact of COVID-19 Lockdowns and social behaviour on the number of Dengue cases in different parts of the world including southeast Asian countries [32][33][34]. But the detailed and systematic analysis of the effect of COVID-19 lockdowns with respect to the social behavior of people on the number of dengue cases in different parts of the world during the pre-pandemic and pandemic of COVID-19 is still not well studied.…”
Section: Introductionmentioning
confidence: 99%
“…In line with a previous literature review ( Mohd-Zaki et al, 2014), this review also found the incidence of dengue in Malaysia to be increasing, with the number of cases exceeding 80,000 annually between 2014-2019. During that period, 2019, a year of severe outbreaks in several countries in Southeast Asia (Cambodia, Indonesia, Lao PDR, Philippines, Thailand, and Vietnam), including Malaysia, recorded the highest dengue incidence (Wiyono et al, 2021), followed by 2015. The rising incidence of dengue is likely due to a number of compounding factors which include urbanisation, shifts in the dominant DENV serotype, vector expansion and climate change (temperature, humidity, and rainfall) which is favourable for breeding of Aedes spp.…”
Section: Discussion (1022 Words)mentioning
confidence: 99%
“…Diagnosis remains difficult as febrile illnesses with common presentation are increasing globally [18]. There was a 46% increase in dengue cases from 2015 to 2019, with a prominent peak in 2019 from Association of Southeast Asian Nations (ASEAN) region [19]. More recent studies during the pre-COVID-19 period (2015-2019) and COVID-19 period (2020-2021) showed average dengue incidences across the 22 major dengue-endemic Asian countries including Nepal and Latin American countries decreasing by 16% during the pandemic period compared to the pre-COVID-19 time (2015-2019), although sporadic increases in the incidences were observed in some countries including Singapore [20].…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies during the pre-COVID-19 period (2015–2019) and COVID-19 period (2020–2021) showed average dengue incidences across the 22 major dengue-endemic Asian countries including Nepal and Latin American countries decreasing by 16% during the pandemic period compared to the pre-COVID-19 time (2015–2019), although sporadic increases in the incidences were observed in some countries including Singapore [ 20 ]. A few cases of COVID-19 and dengue co-infection have been reported from Nepal and other dengue-endemic countries [ 11 , 19 ].…”
Section: Discussionmentioning
confidence: 99%